2019
DOI: 10.18203/2394-6040.ijcmph20191419
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders among women of reproductive age group in an urban area in Bengaluru

Abstract: Background: Common mental disorders are commonly encountered in community settings, especially in women. The somatic symptoms often lead to repeated visits to health care practitioners without resolution of the problem. The knowledge of magnitude of common mental disorders and their associated factors has proved useful in psychiatric epidemiological research.Methods: A community based cross-sectional study was carried out among 480 randomly selected women in the reproductive age group using self-reporting ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…Working women have dual responsibilities both of home and workplace which results in role conflicts and thus more stress predisposing them to poor mental health. Similar findings were reported by Panigrahi et al (2017)(8) in Bhubaneswar and Sathyanarayana et al (2019) (15) in Bangalore. The study also revealed the impact of poor socioeconomic status on presence of common mental disorders.…”
Section: Discussionsupporting
confidence: 89%
“…Working women have dual responsibilities both of home and workplace which results in role conflicts and thus more stress predisposing them to poor mental health. Similar findings were reported by Panigrahi et al (2017)(8) in Bhubaneswar and Sathyanarayana et al (2019) (15) in Bangalore. The study also revealed the impact of poor socioeconomic status on presence of common mental disorders.…”
Section: Discussionsupporting
confidence: 89%
“…The high prevalence reflects the secular trend in CMDs emphasized by global and regional studies (Vos et al, 2016). Relatively lower prevalence was reported from other Indian studies among urban women for instance 22.1% among married women from slums of Bhubaneswar (Panigrahi et al, 2017), 33.5% in a colony in Bengaluru (Sathyanarayana & Manjunatha, 2019), 11.2% to 18.7% from Chennai (Poongothai et al, 2009), 26.7% prevalence of CMDs from a slum in Mumbai (Trivedi et al, 2009). A lower prevalence rate of 33% was reported from an earlier study done in the township of Vellore in a different catchment area amongst primary care attendees (Pothen et al, 2003).…”
Section: Discussionmentioning
confidence: 67%
“…7 However, there were contrasting findings in other Indian studies. For example, Sathyanarayana et 13,14,15 These discrepancies in prevalence rates could be attributed to differences in the screening tools used. The current study used PHQ-9 and GAD-7, while the other three studies used Self Reporting Questionnaire-20.…”
Section: Discussionmentioning
confidence: 99%